CT Coronary Angiography for the follow-up of coronary stent - Cademartiri, F.; Maffei, E.; Palumbo et al., A. (Acta Biomedica Atenei Parmensis, 2010)
The treatment of coronary artery stenosis has progressively shifted over the past decades, from surgical (CABG) to percutaneous (PCI and stenting). The recent introduction of drug-eluting stents further reduced the occurrence of in-stent re-stenosis (ISR). However, a non-negligible number of patients  need imaging/functional tests when symptoms recur. Multi-Slice CT Coronary Angiography (CT-CA) is a clinical reality for the evaluation of coronary artery stenosis, but still under evaluation in the follow-up of coronary stents. Several factors may impair proper depiction of in-stent lumen even with the most recent CT equipments. In highly selected populations CT-CA may play a clinical role even though the performance requirements both from the technical standpoint (i.e. CT scanner) and from the training (i.e. operators’ experience) are still very demanding. In the meantime CT technology should improve towards higher contrast, spatial and temporal resolution in order to achieve the results that may be proper for clinical implementation.